Neonatal hypogonadism due to rare testicular atrophy with congenital contralateral torsion: case report - Antunes Contrucci, Bruno; Rogério Pinato, Gustavo; Manzati Galvani, Camila; Claudino Altomari, Isabela; Camargo Schmidt Neto, Sebastião; Moraes Castro, Júlia; Belone Garcia, Bruna; Mendes Farinazzo, Henrique; Fiuza Tambellini, Giulia; Lomba Corsini, Maria Fernanda; Leite Beneli, Pedro Henrique; Cristina Bortolozzo, Raquel (Brazilian Journal of Case Reports, 2022)
The process of sexual differentiation involves genetic, hormonal and anatomical factors, and there may be several disorders evident at birth. Congenital testicular torsion associated with atrophy contralateral gonad in phenotypically male newborns, without alteration in development of the internal and external genital organs, is a rare condition and little reported in the literature. Thereby, we sought to report and discuss the clinical case which the presence of both clinical conditions was diagnosed in the perinatal period. Hormonal production of testicular androgens is confirmed by the development of the male genital system, both internal and external. It isn’t possible to determine whether the atrophic testis was caused by extrinsic compression of the vascular bundle due to torsion of contralateral testis, or by testicular regression syndrome, in which there in involution of the organ in utero as part of presentation of gonadal dysgenesis. The twisted testicle may have been regression, without hormone production by it, or there was hormonal production of congenitally atrophied testicle and later regressed. Regardless of this fact, early diagnosis is the cornerstone of the clinical condition, since it will invariably evolve with hypergonadotropic hypogonadism, with need for multidisciplinary follow-up.